A novel plantaricin 827 effectively inhibits Staphylococcus aureus and extends shelf life of skim milk. (15th January 2022) - Zhao, Deyin; Wang, Qian; Lu, Fengxia; Bie, Xiaomei; Zhao, Haizhen; Lu, Zhaoxin; Lu, Yingjian
Abstract: Increasing cases of infections by S. aureus in food resulted in a great demand to utilize natural, safe, and effective antimicrobial agents which could inactivate foodborne pathogens in the food industry. A novel class IId bacteriocin, plantaricin 827, produced by Lactobacillus plantarum 163 was isolated and identified. Its molecular mass and amino acid sequence were determined to be 827 Da and N-His-Ser-Ser-Tyr-Gly-Tyr-Asp-OH, respectively. Plantaricin 827 not only possesses thermostable and pH adaptability but also shows a broader antibacterial spectrum. Its antibacterial mechanism against S. aureus increased the cell membrane permeability and integrity, resulting in the leakage of K + and changes in cell morphology. Meanwhile, it inhibited the biofilm formation and interacted with genomic DNA minor groove in AT-rich regions. In addition, plantaricin 827 could significantly inactivate S. aureus in skim milk and extend the shelf life of milk. These results demonstrated that plantaricin 827 could effectively inhibit S. aureus and show the potential to replace chemical preservatives to control foodborne pathogens in dairy products. Highlights: A novel plantaricin 827 was separated and identified. Plantaricin 827 possesses a broader antibacterial spectrum. Plantaricin 827 could combine with the DNA minor groove in AT-rich regions. Plantaricin 827 could effectively inactivate Staphylococcus aureus. Plantaricin 827 significantly extends the shelf life of skim milk.